Dinâmica populacional do camarão cascudo Macrobrachium amazonicum (Heller, 1862) da Ilha de Combú – Belém-PA - SILVA, Márcia Cristina Nylander (Universidade Federal do Pará, 2014)
Shrimps of genus Macrobrachium, family Palaemonidae, are largely utilized for aquaculture and also are explored by commercial fisheries. Amongst the species of this genus, M. amazonicum is largely consumed, shows valued meat and is largely distributed. Considering the social-economic importance of this resource in the State of Pará, this study has the objective of describing the population dynamics and assesses the stock of barky shrimp M. amazonicum in island of the Combú (Pará). Data was collect from March 2002 to February 2003 (except august) where approximately 500 grams of shrimp were monthly obtained. In laboratory, individuals were measured (total length and length of carapace) and weighted (total weight). For determining the fecundity, after removed the eggs mass, were transferred to a water solution were they were counted under a microscopy. For the determination of the population parameters, it was utilized the Program FISAT (Fish Stock Assessment Tools). Females showed smaller maximum length when compared to males, although their average mensal lengths through all year were superior to those of males. It was registered a significant positive sexual proportion to females in July, September, January and February and for the length classes 2.5-2.9 cm and 6.5 to 9.4 cm. The fecundity showed a positive linear relation with the total length and the number of eggs varied from 40 to 3375 eggs/female. It was registered 3 cohorts for the species which were born in December-January/02, September-October/02 and April-May/03. Considering the different methodologies, growth parameters were similar between them and K for males was superior when compared to females and varied from 0.7 to 1.35 cm/month. For females K varied from 0.66 to 0.91 cm/month. L∞ (for most methodologies) was also superior for males (12.37 to 17.66 cm) when compared to females (12.66 to 14.14 cm). Estimated values of total mortality Z for the capture curve had been bigger in the higher for males (values from 3.15 to 6.13) than for females (values from 3.86 to 6.89) the same occurred for method of Beverton and Holt, males (values between 5.43 to 9.31). The length at first capture (Lc) was superior for females (5.88 cm) than for males (4.25 cm). The EMSY (explotation rate for the maximum sustainable yield) for males and females is below the E (exploitation rate) indicating that M. amazonicum of island of the Combú is over-exploited.